2016
DOI: 10.22377/ijgp.v10i3.698
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present review explains reasons of arthritis a disease related to chronic joint pain and inflammation. It also emphasizes the use of bioactive principles of plant origin to be used to relieve from arthritic pain, aching, stiffness, and swelling. These plant natural products can finish rheumatic pain if they are used regularly according to physician' advice. There are so many active crude extracts and pure compounds which show anti-arthritic activity in Freund's complete adjuvant induced animal models. Cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…According to the active ingredient target network diagram, dibutyl phthalate, 9,10-dihydroxy-12Z-octadecenoic acid, Isochlorogenic acid B, Isochlorogenic acid C, Umbelliferone, 1,3-Dicaffeoylquinic acid, 4-Feruloylquinic acid, Caffeic acid, 3-Feruloylquinic acid, 5-Feruloylquinic acid showed as the most potent active components of Heigen. There is accumulating evidence that ICGA exerts several biological activities, such as antioxidant, and anti-inflammatory (Upadhyay, 2016). Previous studies have shown that caffeic acid can induce cell apoptosis in RA-FLS and reduce productions of IL-6 and TNF-α in FLS (Wang et al, 2017), and it as caspase inhibitors have been regarded as an effective strategy for attenuation of cartilage erosion (Fikry et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to the active ingredient target network diagram, dibutyl phthalate, 9,10-dihydroxy-12Z-octadecenoic acid, Isochlorogenic acid B, Isochlorogenic acid C, Umbelliferone, 1,3-Dicaffeoylquinic acid, 4-Feruloylquinic acid, Caffeic acid, 3-Feruloylquinic acid, 5-Feruloylquinic acid showed as the most potent active components of Heigen. There is accumulating evidence that ICGA exerts several biological activities, such as antioxidant, and anti-inflammatory (Upadhyay, 2016). Previous studies have shown that caffeic acid can induce cell apoptosis in RA-FLS and reduce productions of IL-6 and TNF-α in FLS (Wang et al, 2017), and it as caspase inhibitors have been regarded as an effective strategy for attenuation of cartilage erosion (Fikry et al, 2019).…”
Section: Discussionmentioning
confidence: 99%